2014
DOI: 10.1371/journal.pone.0110945
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Response to Subcutaneous Implants in Diabetic Rats

Abstract: Implantation of synthetic matrices and biomedical devices in diabetic individuals has become a common procedure to repair and/or replace biological tissues. However, an adverse foreign body reaction that invariably occurs adjacent to implant devices impairing their function is poorly characterized in the diabetic environment. We investigated the influence of this condition on the abnormal tissue healing response in implants placed subcutaneously in normoglycemic and streptozotocin-induced diabetes in rats. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 30 publications
5
41
0
Order By: Relevance
“…Cutaneous wound healing in streptozotocin‐induced diabetic mice is a model established in the literature . Hyperglycemic condition in streptozotocin‐induced diabetic mice alters inflammation, angiogenesis and fibrogenesis, which result a delayed wound closure and increased scar area . We observed that Bix‐PCL1 nanofiber and Bix‐PCL2 nanofiber‐treated mice exhibited a significant increase in the percentage of wound closure.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Cutaneous wound healing in streptozotocin‐induced diabetic mice is a model established in the literature . Hyperglycemic condition in streptozotocin‐induced diabetic mice alters inflammation, angiogenesis and fibrogenesis, which result a delayed wound closure and increased scar area . We observed that Bix‐PCL1 nanofiber and Bix‐PCL2 nanofiber‐treated mice exhibited a significant increase in the percentage of wound closure.…”
Section: Discussionmentioning
confidence: 73%
“…[65][66][67] Hyperglycemic condition in streptozotocin-induced diabetic mice alters inflammation, angiogenesis and fibrogenesis, which result a delayed wound closure and increased scar area. 66,68 We observed that Bix-PCL1 nanofiber and Bix-PCL2 nanofibertreated mice exhibited a significant increase in the percentage of wound closure. This result suggests that, although the Bixin release from the PCL nanofibers is acting since initial days of wound healing and is more effective than PCL alone, increasing Bixin concentration on PCL higher hydrophobic nanofibers produced an unfavorable healing environment.…”
Section: Discussionmentioning
confidence: 87%
“…In consequence, diabetes affects the cellular response to tissue injury and delays wound healing. In a study conducted on rats it was observed that fibrous formation and presence of foreign body giant cells, the typical features of the foreign body reaction, were attenuated in the hyperglycemic environment [19]. We assume that these effects may contribute to a decreased risk of venous stenosis in patients with indwelling endocardial leads.…”
Section: Discussionmentioning
confidence: 89%
“…(Socarras et al, 2014;Lee et al, 2015;Lytle et al, 2015). (Socarras et al, 2014;Lee et al, 2015;Lytle et al, 2015).…”
Section: Macrophages As Major Players Mediating Capsule Formation In mentioning
confidence: 99%
“…It has been shown that capsular fibrosis appeared after chamber implantation due to an unavoidable foreign body reaction resulting from acute and chronic inflammation. (Socarras et al, 2014;Lee et al, 2015;Lytle et al, 2015). Generally, it is only a few days that acute inflammation could last, depending on the shape, size, and physicochemical properties of the implants .…”
Section: Macrophages As Major Players Mediating Capsule Formation In mentioning
confidence: 99%